Comparison of infection and complication rates associated with transvenous vs. subcutaneous defibrillators in patients with stage 4 chronic kidney disease: a multicenter long-term retrospective follow-up - Schiedat, Fabian; Meuterodt, Benjamin; Prull, Magnus; Aweimer, Assem; Gotzmann, Michael; O’Connor, Stephen; Perings, Christian; Korth, Johannes; Lawo, Thomas; El-Battrawy, Ibrahim; Hanefeld, Christoph; Mügge, Andreas; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Patients with progressive chronic kidney disease (CKD) are at higher risk of infections and complications from cardiac implantable electronic devices (CIED). In patients with a primary or secondary prophylactic indication, implantable cardiac defibrillators (ICD) can prevent sudden cardiac deaths (SCD). We retrospectively compared transvenous-ICD (TV-ICD) and intermuscularly implanted subcutaneous-ICD (S-ICD) associated infections and complication rates together with hospitalizations in recipients with stage 4 kidney disease. Methods We retrospectively analyzed 70 patients from six German centers with stage 4 CKD who received either a prophylactic TV-ICD with a single right ventricular lead, 49 patients, or a S-ICD, 21 patients. Follow-Ups (FU) were performed bi-annually. Results The TV-ICD patients were significantly older. This group had more patients with a history of atrial arrhythmias and more were prescribed anti-arrhythmic medication compared with the S-ICD group. There were no significant differences for other baseline characteristics. The median and interquartile range of FU durations were 55.2 (57.6–69.3) months. During FU, patients with a TV-ICD system experienced significantly more device associated infections (n = 8, 16.3% vs. n = 0; p < 0.05), device-associated complications (n = 13, 26.5% vs. n = 1, 4.8%; p < 0.05) and device associated hospitalizations (n = 10, 20.4% vs. n = 1, 4.8%; p < 0.05). Conclusion In this long-term FU of patients with stage 4 CKD and an indication for a prophylactic ICD, the S-ICD was associated with significantly fewer device associated infections, complications and hospitalizations compared with TV-ICDs.